A Cross-Cultural Comparison of Memorable Tourism Experiences of American and Taiwanese College Students - Kim, Jong-Hyeong (Anatolia, 2013)
This research compares memorable tourism experiences (MTEs) of college students from two countries: the United States and Taiwan. Based on a sample of 599 college students (295 from the United States and 304 from Taiwan), the results showed that five out of the seven MTE factors (hedonism, refreshment, novelty, meaningfulness, and knowledge) were significantly different between the two groups. In addition, the results revealed that the MTE factors of local culture and involvement were perceived to be important by both the groups. The findings of this study highlight which MTE factors should be emphasized upon in designing and promoting tourism programmes for each group separately and which important common factors should be satisfied for all visitors, regardless of cultural orientation.